IC 9437 Evaluation Of The DOSI600 Personal Dosimeter - Robert F. Holub (The National Institute for Occupational Safety and Health (NIOSH), 1995)
The U.S. Bureau of Mines (USBM) has tested a personal dosimeter for measuring radon decay products that is manufactured by Tom Scurry Associates. The tests were made to determine the accuracy of the dosimeter system for record keeping of radiation exposures to radon decay products encountered in mining. The radioactivity-detecting head is based on a design developed by the USBM, and the associated air pump was developed by the manufacturer. The dosimeter system was tested in the USBM radon chamber. The detecting head uses CaF:Dy thermoluminescent phosphors and is mounted on a self-regulating air pump. Batteries supply power sufficient for an 8-h shift. The dosimeter system is worn on the miner's belt. Dosimeter calibration tests were performed by the USBM. In addition, the pumps were tested and evaluated under continuous flow conditions. The results of these tests indicate that the Tom Scurry Associates Model DOSI600 dosimeter is suitable for general use in mines where record keeping for natural radiation exposure is required.